2018
DOI: 10.1051/shsconf/20184200014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of REAP Strategy on Reading Comprehension

Abstract: Abstract. The purposes of this study are to find out the effect of REAP strategy on reading comprehension of the fifth grade elementary students of third cluster of Kotagede Yogyakarta. The research method in this study was quasi-experimental with Pretest-Posttest Control Group Design. The population was all of fifth grade elementary students of third cluster of Kotagede Yogyakarta. The sample was fifth grade students of SD Baluwarti, SD Kotagede 1, and SD Kotagede 5 Yogyakarta that were establised by cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…Both indicated that REAP is an appropriate strategy for reading comprehension, and in this research found that the result of means-score and t-𝑡𝑒𝑠𝑡 proved that hypothesis was accepted. It is also supported by the assertion of some findings [15][16] that REAP has proved giving significant effect to the students' reading comprehension. REAP was not only good for general reading comprehension but also good to promote the students' critical thinking [16].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Both indicated that REAP is an appropriate strategy for reading comprehension, and in this research found that the result of means-score and t-𝑡𝑒𝑠𝑡 proved that hypothesis was accepted. It is also supported by the assertion of some findings [15][16] that REAP has proved giving significant effect to the students' reading comprehension. REAP was not only good for general reading comprehension but also good to promote the students' critical thinking [16].…”
Section: Resultssupporting
confidence: 67%
“…In the experimental group, it is seen that the score in pre-test and post-test is different; the result of post-test is higher than pre-test. The lowest score of the students in the pre-test, before taking the treatment of REAP strategy, is very low(15).To get figured out of pre-test and post-test data description in the experimental class clearly and thoroughly, presents the histogram in the following: From the figure above, it can be seen clearly the differences between both tests; it is seen that the result of the test before applying the REAP strategy in teaching…”
mentioning
confidence: 98%
“…Strategi REAP dapat digunakan baik untuk siswa sekolah dasar hingga menengah. Dalam penelitian Andarini dan Ali terhadap tiga sekolah dasar di Jogjakarta dicapai hasil bahwa strategi REAP memberikan efek yang signifikan dan positif terhadap pemahaman bacaan siswa kelas 5 sekolah dasar (Cahyaningtyas & Mustadi, 2018). Juga penelitian Sukma dan Haryadi tentang penerapan strategi REAP dan Request untuk anak SMP dicapai hasil bahwa strategi REAP lebih efektif dibandingkan strategi tradisional dan strategi Request (Sukma & Haryadi, 2016).…”
Section: Muqoddimah Belajar Aqidah Menggunakan Strategi Reapunclassified